2002
DOI: 10.1007/s004260100075
|View full text |Cite
|
Sign up to set email alerts
|

Effects of delayed auditory feedback on timing of music performance

Abstract: Three experiments examined effects of delayed auditory feedback (DAF) on music performance as a function of the temporal location of feedback onsets within produced inter-onset intervals (IOIs). In Experiment 1, pianists performed isochronous melodies at two production rates with different amounts of DAF. Timing variability decreased for DAF amounts that caused feedback onsets to occur halfway through IOIs (binary subdivisions) in a 500-ms, but not 600-ms, IOI rate condition. In Experiment 2, pianists performe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
49
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(58 citation statements)
references
References 50 publications
6
49
3
Order By: Relevance
“…Pfordresher & Palmer (2002) found reduced timing variability in one of two tempo conditions, relative to the general increase with phase mentioned before. Furthermore, when allowed to choose their own tempo during fixed-delay feedback, participants tended to choose a tempo at which the delays occurred at .5 phase ratios (Experiment 2).…”
Section: The Influence Of Simple Versus Complex Phase Ratiossupporting
confidence: 43%
See 2 more Smart Citations
“…Pfordresher & Palmer (2002) found reduced timing variability in one of two tempo conditions, relative to the general increase with phase mentioned before. Furthermore, when allowed to choose their own tempo during fixed-delay feedback, participants tended to choose a tempo at which the delays occurred at .5 phase ratios (Experiment 2).…”
Section: The Influence Of Simple Versus Complex Phase Ratiossupporting
confidence: 43%
“…Earlier work supports this result. Pfordresher & Palmer (2002) found that the variability of produced timing (an index of timing disruption) increased with delay beyond the 200 ms interval shown to be maximally disruptive in other research (MacKay, 1987). Disruption increased as feedback onsets approached the time of the next action (cf.…”
Section: Feedback Timing and Maximal Disruptionmentioning
confidence: 90%
See 1 more Smart Citation
“…Then participants performed at least two repetitions of that melody from memory in synchrony with the metronome, at the prescribed rate (500 ms between metronome onsets). Then participants performed it with a .66 feedback phase shift (similar to the absolute time delay found to be most disruptive by Pfordresher & Palmer, 2002) at a comfortable self-selected rate for another two repetitions to become accustomed to the experience of altered feedback. Following this familiarization with synchronization and altered auditory feedback, participants performed at least one practice trial using the .66 phase shift.…”
Section: Methodsmentioning
confidence: 99%
“…DAF causes disruption such as slowing of production rate (for music: Finney, 1997;Gates, Bradshaw, & Nettleton, 1974; for speech : Howell, 1983;Howell & Archer, 1984;Howell & Powell, 1987;Howell, Powell, & Khan, 1983; for tapping: R. A. Chase, Harvey, Standfast, Rapin, & Sutton, 1961), increased errors (for music: Finney, 1997; for speech : Fairbanks & Guttman, 1958;MacKay, 1968MacKay, , 1970Robinson, 1972; for tapping : Finney & Warren, 2002), and increased timing variability (for music: Pfordresher & Palmer, 2002). However, Finney (1997) found that randomization of feedback pitches did not disrupt piano performance, in contrast to significant disruption from DAF.…”
mentioning
confidence: 99%